رسول اللہ ﷺ کی ریاست میں زراعت کو فروغ دینے کی حکمت عملی اور اس کے بنیادی اصول - Mehmood Ahmad Khan; Muhammad Sharif (Seerat Studies, 2023)
Abstract Upon setting foot in Yathrib, the Messenger of Allah ﷺ paid special attention to agriculture in accordance with the specific characteristics of the land of Yathrib to economically stabilize the Muslims. Yathrib and its surroundings were highly suitable for agriculture due to their land and climate. In terms of profession, the Prophet ﷺ and his family were connected to trade, initiating their economic life as traders. Similarly, the Meccan Quraysh's main occupation was trade, while the polytheists of Mecca considered agriculture the lowest profession. However, the Messenger of Allah did not consider any legitimate means of earning livelihood superior or inferior. Hence, after the migration to Medina, following establishing ties between the Muhajireen (migrants from Mecca) and the Ansar of Medina, who were already engaged in agriculture, the Prophet ﷺ commanded adopting agriculture for the betterment of their livelihoods. With the directive of the Prophet ﷺ, the Companions also began taking interest in agriculture. Before the arrival of the Messenger of Allah ﷺ in Yathrib, some agricultural principles and regulations existed, which he did not outright reject but rather rectified. He eliminated only those transactions that involved usurious systems or deceitful dealings, establishing Sharia principles. After verifying the correctness of the agricultural system, he emphasized on promoting agriculture and structured practical wisdom based on certain principles. He granted people the right to personal and communal ownership. For the improvement of the economy, he not only commanded agriculture but also personally engaged in it practically. He cultivated some lands himself and allocated some for farming. He instructed people regarding agriculture and farming, establishing principles that would safeguard the rights of landowners and cultivators. Furthermore, he established institutions of endowment (waqf) and treasury (Bait al-Mal) for social benefits.